Review on Sorting Techniques - Saini, Aryan; Kumar, Akshay (Journal of Advanced Research in Signal Processing and Applications, 2023)
There are many popular problems in different practical fields of computer sciences, database applications, Networks and Artificial intelligence. One of these basic operations and problems is sorting algorithm; the sorting problem has attracted a great deal of research. A lot of sorting algorithms have been developed to enhance the performance in terms of computational complexity. There are several factors that must be taken into consideration; time complexity, stability, memory space. Information growth rapidly in our world leads to increase developing sort algorithms.a stable sorting algorithms maintain the relative order of records with equal keys This paper makes a comparison between the Grouping Comparison Sort (GCS) and conventional algorithm such as Selection sort, Quick sort, Insertion sort , Merge sort and Bubble sort with respect execution time to show how this algorithm perform reduce execution time.